34‐4: Simultaneous Scanning Transmission Electron Microscopy, Cathodoluminescence Imaging and EELS of Quantum Dot in Rods. Issue 1 (May 2016) - Fern, George R.; Silver, Jack; Ireland, Terry G.; Howkins, Ashley; Jochum, Tobias; Niehaus, Jan S.; Schröder‐Oeynhausen, Frank; Weller, Horst
Abstract : We show the simultaneous scanning transmission electron microscopy high angle annular dark field, cathodoluminescence imaging and Se electron energy loss spectroscopy maps of a single CdSe/CdS core/shell quantum dot‐in rod. The maps shown align well with significant red light emission within 2.7nm of the Se core.